THE EFFECT OF BLENDED LEARNING STRATEGY ON THE EIGHTH GRADE STUDENTS’ WRITING SKILL OF SMP NEGERI 41 MEDAN IN THE ACADEMIC YEAR OF 2020/2021 - Ketaren, Ceria Br; Lumban Raja, Viator; Prayuda, Meikardo Samuel (Kairos English Language Teaching Journal, 2022)
The purpose of this study was intended to find out the empirical evidence of the students’ achievement in writing descriptive text by using the Blended Learning strategy on the eighth-grade students' writing skill. This study used a quasi-experimental method. The sample in this research was 60 students consisting of 30 students in the experimental group (VIII-1) and 30 students in the control group (VIII-4) taken by purposive sampling. The experimental group has given the treatment using the Blended Learning strategy, while the control group did not use the Blended Learning strategy. Pre-tests were given in two groups before giving treatment. The results showed as follows: First, the pre-test score showed the average score of the experimental group was 56,70 and the control group was 54,37. After being given the treatment, the students of the experimental group was given post-test, as well as the control group, but without treatment. The post-test results show the average value of the experimental group is 83,03 and the control group is 70.53, in this case, the increase in the score of the experimental group is 26,33 and the control class is 16,16. Second, there is a significant difference between post-test and the score of experimental group and control group because the tobserved is 5,10 > 1,697 ttable at the level of significance 0,05. In other words, Ho was rejected and Ha was accepted. In short, it can be concluded that students who write descriptive texts using the Blended Learning strategy are more effective than not using. Thus, it can be concluded that the Blended Learning strategy has a positive influence on the eighth grade students at SMP Negeri 41 Medan in the academic year of 2020/2021.